I See Myself Strong: A Description of an Expressive Poetic Method to Amplify Two-Spirit, Lesbian, Gay, Bisexual, Trans, Queer Indigenous Youth Experiences in a Culture-Centered HIV Prevention Curriculum - Ramona Beltrán; Antonia Rose-Garriga Alvarez; Angela R. Fernandez (Genealogy, 2023)
Poetry is an ideal tool to convey participant voices in social research as it compresses the meaning and essence of participant narratives through using evocative sensory words that illuminate nuances of lived experience. Expressive poetics is an emerging arts-based research method that facilitates a multi-sensory and relational analytical process. In this article, the authors describe and illustrate an adapted expressive poetics research method through highlighting the experiences of Two Spirit, lesbian, gay, transgender, or queer (2SLGBTQ) Indigenous youth that participated in a culture-centered HIV prevention curriculum. It is our hope that through creating dialogic poems, we deepen and nuance the salient experiences of participant youth, acknowledge our relationship through adding our creative response to their calls for care, and create a model for others to engage in a similar process. In a time when 2SLGBTQ bodies are increasingly targeted and policed, it is more important than ever to center and amplify these voices.